The Multivariate Relationship Between Primary Anterior Cruciate Ligament Reconstruction Timing and Revision Rates: A 10-Year Analysis - Brown, Michael; Hurlburt, Gage A; Koenig, Zachary A; Richards, David (Curēus (Palo Alto, CA), 2022)
Background and objective The optimal timing of anterior crucial ligament reconstruction (ACLR) remains a matter of controversy. A revision procedure is performed to improve knee function, correct instability, and enable a safe return to daily function when primary ACLR fails. The present study aimed to determine if the timing of primary ACLR is predictive of revision surgery. Methods All patients who underwent primary ACLR at the West Virginia University from January 2008 to December 2018 were identified. Patients were initially grouped into early (≤30 days) and late (>30 days) ACLR based on the onset of the initial injury. The major outcome measure of this study was the incidence of revision ACLR following primary ACLR. Results A total of 233 primary ACLRs were included. The incidence of ACLR revisions was 9.4%. The timing of primary ACLR, when categorized into early and late ACLRs, was not found to influence revision risk (p=0.384). Additionally, the damaged anatomical structures based on the postoperative diagnosis at the time of ACLR did not influence the odds of revision ACLR (p=0.9721). Conclusion Our study found that the timing of primary ACLR did not influence the revision rates when categorizing primary surgery time into early and late subgroups.